HOW PROTEINS COMMUNICATE: THE MOLECULAR LANGUAGE BEHIND CELL SIGNALING (Journal of Medical & Health Sciences Review, 2025)
Background: Proteins are crucial communicators in cells, converging signaling pathways through smooth interactions and modification that regulate cellular activity and responsiveness.Objective: The current research was conducted to examine how proteins engage with each other through protein-protein interactions (PPIs) and post-translational modifications (PTMs) and how their disruption results in human diseases.Methodology: Qualitative and integrative review of the literature was conducted utilizing peer-reviewed articles from the years 2015–2024, focusing on structural biology, proteomics, and disease models to investigate protein signaling mechanisms.Results: The study identified that PTMs and PPIs like phosphorylation, ubiquitination, acetylation, and methylation play critical roles in ensuring signal fidelity; their deregulation is implicated in cancers, neurodegenerative, and autoimmune diseases.Conclusion: Understanding protein communication language at the molecular level offers valuable insights into mechanisms of disease and a new door toward targeted therapeutic investigation.